Pembentukan Motivasi dan Etos Kerja (Motivation and Work Ethic) Siswa SMK YPP Purworejo - Bambang Sudarsono (Journal of Social Responsibility Projects by Higher Education Forum, 2021)
The purpose of this community service activity is to equip students in improving life attitudes, social mentality and self-development in the process of learning activities so as to form an increase in achievement motivation of SMK YPP Purworejo students in the competency of production machine expertise with 162 participants. This community service activity is carried out using the classical method, which is conveyed in the form of motivation, material exposure and then continued with questions and answers. The results of the implementation of community service are (1) students feel helped and this activity can run quite optimally and students follow it conducively from the start of the event to the end; (2) based on the results of the feedback from the participants, a response was obtained that this activity was very relevant to the needs of vocational school students, especially level XII students who were preparing for the final national exams and who were about to end their study period and (3) the participants felt that they had gained good insight. knowledge about how to learn effectively, and students are more motivated to return to achievement